The handbook of creative writing - Earnshaw, Steven (Edinburgh : Edinburgh University Press, 2007)
An extensive, practical and inspirational resource, this three-in-one volume is aimed at students and practitioners of creative writing at all levels. As well as the main creative writing activities, chapters cover other practices, from translation to st.
Theories of creativity and creative writing pedagogy / Mary Swander, Anna Leahy, and Mary Cantrell -- The evaluation of creative writing at MA level (UK) / Jenny Newman -- The creative writing MFA / Stephanie Vanderslice -- Creative writing and critical theory / Lauri Ramey -- Literary genres / David Rain -- The writer as artist / Steven Earnshaw -- The future of creative writing / Paul Dawson -- Reading, writing and teaching the short story / E.A. Markham -- Writing the memoir / Judith Barrington -- Introduction to the novel / Jane Rogers -- Crime fiction / John Dale -- Writing science fiction and fantasy / Crawford Killian -- How language lives us: reading and writing historical fiction / Brian Kiteley -- Writing humorous fiction / Susan Hubbard -- Writing for children / Alan Brown -- Writing for teenagers / Linda Newbery -- The 'Everything you ever wanted to know about creative nonfiction, but were too naive or uninformed to ask' workshop simulation / Lee Gutkind -- Introduction to poetry / Sean O'Brien -- What is form? / W.N. Herbert -- New poetries / Aaron Kunin -- The poet in the theatre: verse drama / Sean O'Brien -- The sequence and the long poem / George Szirtes -- Introduction to scriptwriting / Mike Harris -- Writing for the stage / Brighde Mullins -- Writing for radio / Mike Harris -- Writing for television / Stephen V. Duncan -- Writing for television: UK differences / John Milne -- Writing for film / Bonnie O'Neill -- Writing as experimental practice / Thalia Field -- Writing as 'therapy' / Fiona Sampson -- Writing in the community / Linda Sargent -- Writing for the web / James Sheard -- The role of the critical essay / Scott McCracken -- Translation / Susan Bassnett -- Creative writing doctorates / Graeme Harper -- How to start a literary magazine / Rebecca Wolff -- How to be a writer / John Milne -- How to present yourself as a writer / Alison Baverstock -- Publishing fiction / Mary Mount -- American pobiz / Chase Twichell -- Publishing poetry in Britain / Sean O'Brien -- The literary agent (novel) / David Smith -- The film agent / Julian Friedmann -- The literary agent: television, theatre and radio / Alan Brodie -- Copyright / Shay Humphrey, with Lee Penhaligan -- Literary life: prizes, anthologies, festivals, reviewing, grants / Tom Shapcott -- The writer as teacher / Gareth Creer -- Making a living as a writer / Livi Michael.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Creative writing; Création littéraire.; LANGUAGE ARTS & DISCIPLINES -- Authorship; Literature; Creative writing; Schrijven; Bellettrie